1981
DOI: 10.1002/pssa.2210660231
|View full text |Cite
|
Sign up to set email alerts
|

A critical examination of the law of approach to saturation. I. Fit procedure

Abstract: The numerical influence of different terms in the law of approach to saturation is tested applying a least square procedure on a variety of sets of synthetical data (256 I ( H ) points) which are generated using the formula I = I,[1 -( A / H ) -(B/H2) -(C/Hs)] + X H + D m. Graphical methods are compared with the fitting procedure. Practical examples applying different methods analysing the I versus H curve of hexagonal polycrystalline cobalt and barium ferrite are given. Die numerischen Verhiiltnisse der versc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(53 citation statements)
references
References 20 publications
1
52
0
Order By: Relevance
“…The term w 0 H becomes more significant when the sample approaches the Curie temperature. However, experimental measurements [99,100] indicated that, in the case of the nanoparticles, a relation of the following form is often sufficient [3,100,101]: …”
Section: Hysteresis Magnetic Behavior Of Nanoparticlesmentioning
confidence: 99%
“…The term w 0 H becomes more significant when the sample approaches the Curie temperature. However, experimental measurements [99,100] indicated that, in the case of the nanoparticles, a relation of the following form is often sufficient [3,100,101]: …”
Section: Hysteresis Magnetic Behavior Of Nanoparticlesmentioning
confidence: 99%
“…So, one have to found some criteria in order to retain only the few pertinent terms involved in the studied case, and for this, different plots have been proposed and rather fully discussed in the past [23,25]. Often, one of the best way is to plot M as function of 1/H because in that case the paraprocess terms make the curve rising up at the low 1/H values (high fields) while the p ¼ À2 term give a negative curvature in the high 1/H range.…”
mentioning
confidence: 99%
“…The magnetic parameters such as saturation magnetization (M s ), coercivity (H c ), retentivity (M r ) and squareness ratio (M r /M s ) values were obtained from these loops. The values of saturation magnetization (M s ) were calculated by the law of approach (LoA)to saturation[20][21][22] and the fitted curves of M s calculated by this law at different temperatures The following law of approach to saturation was used to obtain the fitted data and this data were fitted by using a least-squares procedure [s is saturation magnetization, A represents the inhomogeneities in the sample, B is proportional to K 2 (K is the anisotropy constant), H is the applied field and χ is the magneticsusceptibility. The saturation magnetization (M s ) and the coercivity (H c ) of the sample were in the range, 49.4-67.9emu/g and 207-1983Oe, respectively, depending on the heat treatment temperature (800 ∼ 1200°C).…”
mentioning
confidence: 99%